Implementasi Pengendali PID Untuk Kestabilan Posisi Terbang Wahana Tanpa Awak - Christin P.R. Tuuk; Vecky C. Poekoel; Jane Litouw (Jurnal Teknik Elektro dan Komputer, 2018)
Abstract — Unmanned aircraft or UAV (Unmanned Aerial Vehicle) with remote control is an electromechanical that can perform programmed missions. The control process of the aircraft is entirely done by the autopilot system with reference to parameters that have been determined by the user before flying. On unmanned aircraft also needed stability when in the air. Aircraft stability is the ability to return to a certain position in a flight. Ardupilot Mega (APM) is a qualified autopilot IMU (Inertia Measurement Unit).The application of ardupilot with the determination of the PID value regulates the pitching and rolling of the plane to be stable. The PID value for automatic mode obtained from the unmanned rides is for rolling P = 0.4, I = 0.4, D = 0.020 and pitching P = 0.4, I = 0.4, D = 0.020. The unmanned spacecraft has been able to fly in the air steadily, as the aircraft flies from one level of altitude to another.Keywords — Ardupilot, PID Controller, Stability, Unmanned Aerial Vehicle Abstrak — Pesawat tanpa awak atau UAV (Unmanned Aerial Vehicle) dengan pengendalian jarak jauh merupakan elektromekanik yang dapat melakukan misi-misi terprogram. Proses kontrol pesawat sepenuhnya dilakukan oleh sistem autopilot dengan mengacu pada parameter-parameter yang telah ditentukan oleh pengguna sebelum terbang. Pada pesawat tanpa awak juga dibutuhkan kestabilan pada saat di udara. Stabilitas pesawat adalah kemampuan untuk kembali ke posisi tertentu dalam suatu penerbangan. Ardupilot Mega (APM) adalah autopilot IMU (Inertia Measurement Unit) berkualitas. Penerapan ardupilot dengan penentuan nilai PID mengatur pitching dan rolling dari pesawat untuk bisa stabil . Adapun nilai PID untuk mode otomatis yang didapat dari hasil rancang bangun wahana tanpa awak ini yaitu, untuk rolling P=0.4, I=0.4, D=0.020 dan pitching P=0.4, I=0.4, D=0.020 . Wahana tanpa awak yang dibuat sudah dapat terbang di udara dengan stabil, saat pesawat terbang dari satu level ketinggian ke level yang lain.Kata kunci — Ardupilot, Kestabilan, Pengendali PID, Unmanned Aerial Vehicle